2011
DOI: 10.1097/igc.0b013e31820731bb
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Results and Surgical Morbidity of Laparoscopic Nerve-Sparing Radical Hysterectomy in the Treatment of FIGO Stage IB Cervical Cancer: Long-Term Follow-Up

Abstract: A laparoscopic NSRH for FIGO stage IB cervical cancer was comparable to open NSRH in terms of early recovery of bladder function. It did not compromise surgical radicality, but revealed high urological complications, long operating time, and much blood loss, compared with conventional radical hysterectomy. However, these surgical morbidities were corrected with increase in experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
1
33
1
Order By: Relevance
“…In support of this, several other studies have found that blood loss and the length of hospitalization were significantly reduced when undergoing an RRH surgery. 20,26,30 Contrary to this result, another study reported no benefit of RRH over TLRH treatment for cervical cancer patients. 13 In comparison with previously published reports, we have looked at many Data are presented as mean T SD or as percentage (%) of the total number (n).…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…In support of this, several other studies have found that blood loss and the length of hospitalization were significantly reduced when undergoing an RRH surgery. 20,26,30 Contrary to this result, another study reported no benefit of RRH over TLRH treatment for cervical cancer patients. 13 In comparison with previously published reports, we have looked at many Data are presented as mean T SD or as percentage (%) of the total number (n).…”
Section: Discussioncontrasting
confidence: 42%
“…16,20 In contrast to this, other studies have demonstrated that no significant benefits exist comparing the RRH and TLRH procedure. 23,24 Based on these contradictory findings larger studies are required to compare RRH with TLRH treatment to evaluate the benefits of this expensive surgical procedure.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…However, with the increasing use of advanced technology, more complex surgeries are now being performed laparoscopically. Due to their complexity, the average time of these type of laparoscopic operations are usually greater than three hours (Fagevik Olsen M 1999, Kuo et al 2013, Park et al 2011. In these studies, the PPC incidence between open and laparoscopic surgery is similar, suggesting that there may be an increased PPC risk in prolonged laparoscopic surgery (Kuo et al 2013, Park et al 2011.…”
Section: Postoperative Breathing Exercisesmentioning
confidence: 66%
“…Due to their complexity, the average time of these type of laparoscopic operations are usually greater than three hours (Fagevik Olsen M 1999, Kuo et al 2013, Park et al 2011. In these studies, the PPC incidence between open and laparoscopic surgery is similar, suggesting that there may be an increased PPC risk in prolonged laparoscopic surgery (Kuo et al 2013, Park et al 2011. This needs to be confirmed with prospective observational studies to enable risk prediction models to be developed, which will in turn assist physiotherapists and hospitals to determine which patients require targeted PPC prophylaxis following these newer types of procedures.…”
Section: Postoperative Breathing Exercisesmentioning
confidence: 99%